2019
DOI: 10.3390/en12183405
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Gas Production from Gas Shale Reservoirs—Influence of Gas Sorption Hysteresis

Abstract: The true contribution of gas desorption to shale gas production is often overshadowed by the use of adsorption isotherms for desorbed gas calculations on the assumption that both processes are identical under high pressure, high temperature conditions. In this study, three shale samples were used to study the adsorption and desorption isotherms of methane at a temperature of 80 °C, using volumetric method. The resulting isotherms were modeled using the Langmuir model, following the conversion of measured exces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…The nanoscale pores in the shale constitute a complex pore network [6][7][8][9]. In particular, the micropores (pore diameter <2 nm) and mesopores (2-50 nm) have the characteristics of a large specific surface area and high degree of heterogeneity, thereby increasing the complexity of the accumulation and migration mechanism of shale gas [10][11][12][13][14]. The difficulty in the characterization of shale reservoirs is the quantitative description of micropore and mesopore structures.…”
Section: Introductionmentioning
confidence: 99%
“…The nanoscale pores in the shale constitute a complex pore network [6][7][8][9]. In particular, the micropores (pore diameter <2 nm) and mesopores (2-50 nm) have the characteristics of a large specific surface area and high degree of heterogeneity, thereby increasing the complexity of the accumulation and migration mechanism of shale gas [10][11][12][13][14]. The difficulty in the characterization of shale reservoirs is the quantitative description of micropore and mesopore structures.…”
Section: Introductionmentioning
confidence: 99%
“…This percentage could be as high as 60-85% for organic-rich shale [6]. Previous studies suggested that the total GIP in shale reservoirs is affected by the total organic carbon (TOC) content, organic matter type, thermal maturity, and pore structure [7,8]. Wu et al carried out adsorption experiments of light hydrocarbons and carbon dioxide on shale samples and isolated kerogen, respectively [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven in Section that a linear decline in the Gibbs adsorption isotherm is due to the Gibbs discarded amount ρ v a, which was subtracted from mass balance calculation. Hence, it is reasonable to use the intercept method , to calculate the saturated density of adsorbed phase according to the physical meaning of the linear decline (see Figure ). However, the intercept method can only obtain the saturated density for the linear descending part.…”
Section: Discussionmentioning
confidence: 99%
“…However, some research studies , have reported that the physical adsorbents such as coal and shale also have a negative adsorption phenomenon, that is, the adsorption isotherm exhibits a distinct decline at relatively higher pressure instead of a widely accepted type I isotherm. Even more unfortunately, the negative adsorption phenomenon gives rise to two challenging difficulties in adsorption isotherm measurement; one is mass balance miscalculation , and the other is negative adsorption isotherm calibration. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation